Dentigerous cyst associated with an ectopic third molar in the maxillary sinus: A rare entity - Srinivasa Prasad T; Sujatha G; Niazi Thanvir; Rajesh P (Wolters Kluwer Medknow Publications, 2007)
Ectopic eruption of teeth into a region other than the oral cavity is rare although there have been reports of teeth in the nasal septum, mandibular condyle, coronoid process, palate, chin and maxillary sinus. Occasionally, a tooth may erupt in the maxillary sinus and present with local sinonasal symptoms attributed to chronic sinusitis. We present a case of an ectopic maxillary third molar tooth that caused chronic purulent sinusitis in relation to the right maxillary sinus.